Approche diachronique des sites de hauteur des âges des Métaux, de l'Antiquité tardive et du haut Moyen Âge - Martinez, Damien; Quiquerez, Amélie (Monographies et Actes de colloques, 2023)
The study of fortified hilltop settlements is one of the most important topics in territorial and settlement archaeology, especially for the Metal Ages, Late Antiquity, and the Early Middle Ages. Nevertheless, the long-term dynamics of hilltop settlements is still poorly understood, both in terms of intra-site dynamics as well as at a territorial scale. This is the major original focus of the one-day workshop held on November 12, 2019, by the research team "Fabrique du Paysage" of the UMR ARTEHIS, resulting in the contributions presented in this publication. The comparative approach between Protohistory and the Early Middle Ages, beyond a confrontation of settlement modes and the analysis of the spatial patterns shared by the two periods, is also intended to be methodological, with the main objective of establishing the first steps for a durable dialogue amongst experts. Through six contributions presenting the results of investigations on sites located in the Auvergne, the Vosges, and the present-day Bourgogne-Franche-Comté region, this publication explores new perspectives and recommends increased collaboration between specialists of the two main chronological fields. Ultimately, this study constitutes a preliminary contribution, encouraging the renewal of initiatives to increase our understanding of the relationships between long-term settlement dynamics and landscape evolution.